ANALISIS PERCEIVED VALUE KONSUMEN TERHADAP eWOM DENGAN ATTITUDE DAN SATISFACTION SEBAGAI MEDIASI PADA PERILAKU BELANJA TIKTOK SHOP - PUTRI, ANGGUN ANGGITA KINASIH SUNOWO (PRIMA EKONOMIKA, 2024)
The development of digital technology has caused a shift in the way consumers search for information and make purchases. One of them is through e-commerce platforms such as TikTok Shop. However, in its development, there are various problems that arise related to transactions at TikTok Shop. This problem can certainly cause consumer dissatisfaction with TikTok Shop. Based on previous research, consumer dissatisfaction can affect negative eWOM which will have an impact on consumer value perceptions of TikTok Shop. This study aims to test the effect of perceived value on e-WOM with consumer attitudes and satisfaction as mediating variables on TikTok Shop consumers. This study uses a quantitative descriptive and explanatory approach and the sample of this study is consumers who have shopped at TikTok Shop with a non-probability sampling method and purposive sampling technique. By using 205 respondents, the data analysis used Structural Equation Modeling through AMOS. The results of the study showed that perceived value had a significant positive effect on attitudes, satisfaction and eWOM, while attitudes had a significant negative effect on eWOM and satisfaction had a significant positive effect on eWOM. Keywords: Perceived Value ; Attitude; Satisfaction; eWOM ;Tiktok Shop